Carbon aerogel reinforced PDMS nanocomposites with controllable and hierarchical microstructures for multifunctional wearable devices. (January 2021) - Sun, Yan; Li, Deping; Kim, Jong Uk; Li, Bing; Cho, Seung-Hyun; Kim, Tae-il; Nam, Jae-Do; Ci, Lijie; Suhr, Jonghwan
Abstract: Wearable devices have attracted increasing attention for development of personal healthcare. In this study, three-dimensional porous carbon aerogels reinforced polydimethylsiloxane nanocomposites with controllable and hierarchical open, semi-open and closed cell structures were developed for multifunctional wearable heating and sensing devices. This investigation reveals that the microstructures of the aerogels play a critical role in determining nanocomposites properties, particularly their heating and sensing performances. As thermotherapy heaters, the nanocomposite with semi-open cell structure is observed with the highest energy transduction efficiency (equilibrium temperature ∼138.9 °C under only 5 V) compared to the nanocomposites with open and closed cell structures, due to the well-defined conductive network and structural stability. As stimuli-responsive sensors, compared to the nanocomposite with closed cell structure, the nanocomposites with open and semi-open cell structures are observed with higher sensitivity (gauge factor ∼369.03) and much better repeatability, benefiting from their structural integrity. Finally, the nanocomposite with semi-open cell structure was investigated for practical potential on human body. Experimental results demonstrated the uniform temperature distribution and reliable sensitivity as a multifunctional wearable device. Therefore, by controlling and optimizing the microstructure of carbon aerogels, the nanocomposites with tailored microstructure could be exploited for various engineering applications including emerging multifunctional wearable devices. Graphical abstract: Image 1